Kreatorzy, gestorzy i internauci – od baz danych przestrzennych do map numerycznych i wirtualnych globusów - Piotr Werner, Piotr Werner (Człowiek i Społeczeństwo, 2013)
The basic elements of Geographic Information Systems are spatial databases. There are multiply interfaces of views and queries as well as methods of reporting. They are multi-resolution and multi-representations. Additional elements are standardized metadata. Currently they are developing as the technologies of distributed processing using wireless networks and global positioning systems. The procedures of spatial data bases creation are based on well recognized and defined methodology. Recent development of Information and Communication Technologies (ICT) is the cause that traditional division of work concerning spatial databases among authors, administrators and users changes itself. Directional propagation of information (according to Shannon theory) from authors through administrators to users is changing. Users are simultaneously authors and administrators, sharing their own collections of spatial data and vice versa, sometimes professionals use such collections supporting and updating professional spatial databases using public access data. Creation, assembling and dissemination of spatial data provided voluntarily by individuals has been defined as Volunteered Geographic Information. There are a lot of impacts of this new trend involving essential, legal and economic aspects as well as creating the new qualities in culture of the societies.